AN ANALYSIS OF LISTENING COMPREHENSION ROLE IN IMPROVING STUDENT’S SPEAKING ABILITY AT ENGLISH STUDY PROGRAM ISLAMIC UNIVERSITY OF INDRAGIRI - Fatkhul Budiman; Melda Yeni; Agus Mustajib (Program Studi Pendidikan Bahasa Inggris, 2022)
This study aims to determine the role of listening comprehension in improving students speaking ability at English Study Program Islamic University of Indragiri. This type of research is descriptive quantitative. The population of this research is the students of English Study Program at Islamic University of Indragiri. The number of population and samples from this study were 36 people, taken using a total sampling technique. To determine the role of listening comprehension in improving students speaking ability, the researcher gave a questionnaire as an instrument. For data analysis, researchers used Likert scale as a measurement of the variables. The test results show the role of listening comprehension in improving students speaking ability at English Study Program Islamic University of Indragiri is in a high level with an average of 132.4. The researcher concludes that listening comprehension has a great role in improving students speaking ability at English Study Program Islamic University of Indragiri.